Impact of penetration schemes to optimal DG placement for loss minimisation. Issue 5 (28th May 2017) - Gkaidatzis, Paschalis A.; Doukas, Dimitrios I.; Bouhouras, Aggelos S.; Sgouras, Kallisthenis I.; Labridis, Dimitris P.
Abstract : This paper examines the impact of different penetration schemes to the optimal distributed generation placement problem for loss minimisation. The four variables of the problem are presented and a concept based on degrees of freedom (DoF), representing the number of the variables that undergo any kind of limitation during the solution process, is introduced. Four commonly utilised penetration schemes subject to various limitations are examined and compared with a fifth penetration scheme, which is unconstrained and is proposed as the optimal one. All schemes are implemented under a local-particle swarm optimisation-variant algorithm and applied on the IEEE 33 and IEEE 118 bus systems. The results indicate that the proposed penetration scheme with four DoF provides the optimal solution both in terms of loss minimisation and voltage profile improvement.